PELATIHAN LAPORAN KEUANGAN SYARIAH BAGI ENTREPRENEUR MUDA DI MAKASSAR - Amin, Asbi; Astuti, Niken Probondani (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2019)
Training on sharia financial statements for young entrepreneurs in Makassar aims to train young people who already have business in preparing and subsequently making sharia financial reports. Islamic financial statements are needed for decision making for the business owners themselves and outside parties. The method of implementation is carried out by conducting counseling, training sharia financial reports and mentoring. The final goal of this service is for young entrepreneurs to be able to understand and take notes on Islamic financial statements.